Fundamentals of solid state engineering. - Razeghi, Manijeh (Springer Berlin Heidelberg, 2019)
Fundamentals of Solid State Engineering is structured in two major parts. It first addresses the basic physics concepts, which are at the base of solid state matter in general and semiconductors in particular. The second part reviews the technology for modern Solid State Engineering. This includes a review of compound semiconductor bulk and epitaxial thin films growth techniques, followed by a description of current semiconductor device processing and nano-fabrication technologies. A few examples of semiconductor devices and a description of their theory of operational are then discussed, including transistors, semiconductor lasers, and photodetectors.